O07-5 Cancer and work: work functioning trajectories in cancer patients. (1st September 2016) - Dorland, Heleen; Abma, Femke; Roelen, Corne; Stewart, Roy; Amick, Benjamin; Ranchor, Adelita; Bultmann, Ute
Abstract : Objectives: To date, little is known about how cancer patients function at work after return to work and which factors are associated with work functioning over time. Hence, the aims of the study were 1) to identify trajectories of work functioning in cancer patients who had returned to work over 1-year follow-up and 2) to determine factors associated with trajectory group membership from individual, clinical and psychosocial characteristics. Methods: We used data from N = 372 cancer patients who had returned to work after a diagnosis of cancer. Data were collected at baseline and at 3, 6, 9 and 12 months follow-up. The Work Role Functioning Questionnaire 2.0 was used to assess work functioning. Latent Class Growth Modelling was used to identify trajectory groups of work functioning and the impact of individual clinical and psychological characteristics on trajectory group membership. Results: A six-class trajectory was chosen as best fitting and substantively meaningful model for work functioning over 1-year follow-up. Three groups (63% of the study sample) represented with high-stable scores for work functioning over time (WRFQ mean = 99, mean = 94 and mean = 85); group 4 (21%) had medium-stable scores (WRFQ mean = 69) over the 1-year follow-up period, group 5 (11%) consisted of cancer patients with low-stable scores (WRFQ mean = 50) and group 6 (5%) had increasing scores over time (WRFQ mean = 81). Age, education, cancer type, treatment, fatigue, cognitive symptoms and depression were differentially associated with the work functioning groups. Conclusion: Distinct trajectories of work functioning in cancer patients, who had returned to work, were identified. Individual, clinical and psychological characteristics were associated with group membership. Occupational health care providers should be aware of the course of work functioning over time in cancer patients after return to work and may monitor work functioning closely after return to work.